Puberty and Character Education Model in Primary School - Erry Utomo; Nurfadhilah (Indonesian Journal Of Educational Research and Review, 2022)
Education is sought to sharpen the character of students, involving teachers, parents, and the community. Teachers and parents are still difficult to convey information regarding reproductive health and sexuality. The study aims to provide a hypothetical model of puberty and character education to be implemented in a primary school in Indonesia. Methods used in the study were an online survey for teachers and a qualitative approach to develop a hypothetical model based on the Health Belief Model. Data collections are questionnaire, interviews and/or discussions to deepen the respondents' statements. The data analysis is use descriptive analysis of variables in the model. The result shows that teachers perceived the knowledge and behavior of students vary widely. The consequences that may occur are also quite serious. Perceived benefits are mostly pointed at students. Perceived barriers and vice versa, include the point of view of teachers and facilities, although the characteristics of students that are difficult to recognize and control are perceived as the dominant factor as well. The puberty education that is carried out is also very much in line with the strengthening of character education. It is highly recommended that puberty education be applied in primary schools in Indonesia.